Fahr Disease : A Case Repor - Abdulmannan, Adamilzary Fikry; Prodjokusumo, Hafidz Muhammad; Rahman, Putri Windiana; Fitriana, Rizni; Kurnia, Achdi (Sanus Medical Journal, 2025)
In Indonesia, life expectancy has risen significantly. The rise in life expectancy is, of course, directly proportional to the rise in the elderly population (elderly). Coronary heart disease, hypertension, metabolic disorders, and arthritis are all problems that the elderly face on a daily basis. To improve the quality of life of the elderly, preventive efforts that are tailored to their physiological needs are required. However, descriptive data on the parameters to be examined in this group are required before conducting an intervention. The authors are encouraged to know the description of total cholesterol levels in the elderly who are in the DPC Muhammadiyah Pondok Aren environment based on the background of the problems described above. Glucose, hemoglobin, and total cholesterol levels in plasma will be measured. This study collects primary data from respondents by taking finger blood samples, which are then measured using the Easy Touch® tool. Total sampling was used, and the number of samples that met the inclusion criteria was 13 people. The data is analyzed to generate distributions and percentages. The findings revealed that 85.19 percent of the elderly had normal blood glucose levels. According to age, the elderly aged 60-74 years have 83.33 percent normal blood glucose levels, while the elderly aged 75-70 years have 86.67 percent normal blood glucose levels. According to gender, elderly men with normal blood glucose levels account for approximately 84.21 percent of the population, while elderly women with normal blood glucose levels account for approximately 87.50 percent. It was determined that over half of the elderly in PSTW